(untitled) (Teaching and Learning Inquiry, 2020)
To determine factors that influence faculty engagement and success in faculty learning communities focused on collaborative Scholarship of Teaching and Learning (SoTL), our project gathered information on (1) faculty motivation to engage with SoTL; (2) structures that support collaboration; (3) the perceived impact of SoTL on teaching, scholarship, and faculty engagement in academic communities on campus and beyond; and (4) the role of the teaching center in supporting collaborative faculty learning communities focused on SoTL. In this explanatory, sequential design mixed-methods study, participants were asked to complete a survey on their experience as participants in faculty learning communities at a large comprehensive public university in the southeastern United States; researchers then conducted one-on-one interviews with select participants to gain an in-depth understanding of trends and questions emerging from the survey data. Results indicate that personal, institutional, professional, and team factors contribute to participants’ perception of the success and effectiveness of collaborative research teams. Findings from the study offer guidance for setting up effective collaborative structures for SoTL projects and nurturing inter-disciplinary research among faculty members, thus providing insights that can inform the design and facilitation of similar programs in the United States and internationally.